The communication channel which generates the most demand for Voluntary Medical Male Circumcision at Ndola Central Hospital - Masebo, Bruce Kanene (Journal of Health Informatics in Africa, 2016)
Background and Purpose: It has been demonstrated that male circumcision has numerous health benefits. Various channels of communication are used to disseminate information about male circumcision. The objective of this study was to identify the communication channels which generate the most demand for voluntary medical male circumcision (VMMC) at Ndola Central Hospital (NCH).Methods: All clients aged16 years or older who came for VMMC at NCH in a period of 3 months (01/02/15 to 01/05/15) were captured in the study. A structured questionnaire was used to collect data.  Data entry and analysis were conducted using Epi Data version 3.1 and SPSS version 16.0, respectively. The Pearson’s Chi-square and the Fisher’s exact tests were used to establish associations.  The cut off point for statistical significance was set at the 5% level.Results: A total of 94 individuals participated in this study. Participants who were 16-24 years were motivated by Community leaders (22.3%), Television (22.3%) and Friends (20.2%). The 25+ age group cited Television (18.1%), Radio (18.1%) and Friends (18.1%) as the channels that generated most of their interest for VMMC. Overall, the highest demand to undergo VMMC was generated by Television (40.4%). 66% of participants believed that women are better promoters of VMMC. About 3 in 4 (78%) of the participants had to seek second opinion before undergoing VMMC.Conclusions: Television as a channel that generated most of the interest for VMMC should be used in order to increase uptake of VMMC.